Thin films of ZnO and ZnMnO by atomic layer epitaxy - Wójcik, Aleksandra; Kopalko, Krzysztof; Godlewski, Marek; Łusakowska, Elżbieta; Guziewicz, Elżbieta; Minikayev, Roman; Paszkowicz, Wojciech; Świątek, Krzysztof; Klepka, Marcin; Jakieła, Rafał; Kiecana, Michał; Sawicki, Maciej; et al. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
We discuss properties of thin films of ZnO and ZnMnO grown with atomic layer epitaxy using new, organic zinc and manganese precursors. Several characterization techniques, including X-ray diffraction, atomic force microscopy, scanning electron microscopy, cathodoluminescence, superconducting quantum interfernece device (SQUID) and electron spin resonance, show good topography of the films and their advantageous optical and magnetic properties.
Optica Applicata, Vol. 35, 2005, nr 3, s. 413-417
Keywords: optyka; ZnO; magnetism; low temperature growth; organic precursors